Electron impact on vibrationally cold HF+. (22nd November 2016) - Stroe, Marius Cristian; Fifirig, Magda
Abstract: The dissociative recombination and vibrational excitation processes induced by electron impact on vibrationally cold HF + are investigated in the framework of the multichannel quantum defect theory for electron energies below 1 eV. The thermal rate coefficients for the electron temperature range from 10 to 5000 K are reported.